2020
DOI: 10.3390/agronomy10070984
|View full text |Cite
|
Sign up to set email alerts
|

A Gaussian-Process-Based Global Sensitivity Analysis of Cultivar Trait Parameters in APSIM-Sugar Model: Special Reference to Environmental and Management Conditions in Thailand

Abstract: Process-based crop models are advantageous for the identification of management strategies to cope with both temporal and spatial variability of sugarcane yield. However, global optimization of such models is often computationally expensive. Therefore, we performed global sensitivity analysis based on Gaussian process emulation to evaluate the sensitivity of cane dry weight to trait parameters implemented in the Agricultural Productions System Simulator (APSIM)-Sugar model under selected environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Although the APSIM-Sugarcane model does not contain rue and transp_eff_cf among the cultivar-specific parameters, they were included in the current study because Sexton et al [29] have identified rue as a highly sensitive parameter for biomass yield estimation and transp_eff_cf as a highly sensitive parameter for biomass yield estimation under water stress conditions. Bandara et al [27] have obtained similar results related to rue and transp_eff_cf for estimation of CDW. If the supply of soil water is not a growth-limiting factor, the APSIM-Sugarcane model controls dry matter assimilation via radiation interception and rue.…”
Section: Apsim Simulationsupporting
confidence: 53%
See 3 more Smart Citations
“…Although the APSIM-Sugarcane model does not contain rue and transp_eff_cf among the cultivar-specific parameters, they were included in the current study because Sexton et al [29] have identified rue as a highly sensitive parameter for biomass yield estimation and transp_eff_cf as a highly sensitive parameter for biomass yield estimation under water stress conditions. Bandara et al [27] have obtained similar results related to rue and transp_eff_cf for estimation of CDW. If the supply of soil water is not a growth-limiting factor, the APSIM-Sugarcane model controls dry matter assimilation via radiation interception and rue.…”
Section: Apsim Simulationsupporting
confidence: 53%
“…Parameter ensembles were prepared by using 500 random numbers which are distributed uniformly between the maximum and minimum values of each parameter space (Table 3: Parameter space) using functions in R [38] software. Reasonable values for the parameter spaces were selected based on the descriptions of previous studies of Bandara et al [27] and Sexton et al [22,29].…”
Section: Building Emulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an effort to address these challenges, we analysed to what extent the integration of crop models and phenological monitoring can help reduce these design and temporal basis risks, respectively. Biophysical crop simulation models can be leveraged to generate larger synthetic yield datasets, which can then be used to train weather-or satellite-based index models [18][19][20] or support spatial targeting of limited numbers of CCEs that can be conducted as part of area-yield insurance products. However, to date, this approach has not been widely applied in the context of index insurance design, with limited evidence about its performance at spatial scales relevant for insurance applications (e.g., field, farm or village) or in comparison with index models derived empirically from available observational yield datasets.…”
Section: Introductionmentioning
confidence: 99%